2016
DOI: 10.1155/2016/7830182
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects of Plant Growth Promoting Rhizobacteria and Chitosan onIn VitroSeeds Germination, Greenhouse Growth, and Nutrient Uptake of Maize (Zea maysL.)

Abstract: This study aimed to assess the effects of three plant growth promoting rhizobacteria (PGPR) and chitosan either singly or in combination on maize seeds germination and growth and nutrient uptake. Maize seeds were treated with chitosan and bacterial solution. The germination and growth tests were carried out in square Petri dishes and plastic pots. The combination chitosan-A. lipoferum-P. fluorescens has increased the seeds vigor index up to 36.44% compared to the control. In comparison to the control, P. putid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 22 publications
3
51
1
1
Order By: Relevance
“…Among the minerals studied, Cu was the most effective metal in terms of the inhibition of plant roots [24][25]. At the same time, similar to an earlier study, our results indicated that Cu is an essential nutrient for plants, and that the amount of Cu absorbed is a stimulant for root development and seed germination [26]. The positive correlation between root length and K concentration in the sediment indicated that K is also one of the most important nutrients and is essential for plant growth and development [27].…”
Section: Resultssupporting
confidence: 89%
“…Among the minerals studied, Cu was the most effective metal in terms of the inhibition of plant roots [24][25]. At the same time, similar to an earlier study, our results indicated that Cu is an essential nutrient for plants, and that the amount of Cu absorbed is a stimulant for root development and seed germination [26]. The positive correlation between root length and K concentration in the sediment indicated that K is also one of the most important nutrients and is essential for plant growth and development [27].…”
Section: Resultssupporting
confidence: 89%
“…Gupta et al (2012) reported 23% and 16% increases in leaf area of chickpea following exogenous applications of Put and benzyl adenine under water stress condition. Agbodjato et al (2016) and Gholami et al (2009) reported 45% and 91% enhancement in leaf area of maize under stress condition due to inoculation with A. lipoferum.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these conditions were apparently favorable in this study (application of chitosan), since no negative effects were observed. Several studies reported that chitosan stimulated seed germination in maize (Guan et al, 2009;Lizárraga-Paulín et al, 2011;Agbodjato et al, 2016) and in other plants (Zeng and Luo, 2012;Mahdav and Rahimi, 2013).…”
Section: Discussionmentioning
confidence: 99%